Determination of Acousto-Optic Spatial Filters Diffracted Light at Zeroth-Order Using MATLAB Analysis - Mohammad, Elham Jasim (Newest Updates in Physical Science Research Vol. 9, 2021)
This paper introduces the essentials of acousto-optics with the theory and applications using MATLAB. There are some software used to process acousto-optics filter and the implementation details of any acousto-optics algorithm are inaccessible. Our work is focused on software used to solving the coupled equations in Bragg diffraction by creating MATLAB function for use in Bragg regime and acoustic-optic spatial filtering and employing mainly the MATLAB program for solving this problem. We review the role of acousto-optic and spatial filtering for high-pass spatial filtering. Classically, acousto-optic interactions comprise scattering of photons by energetic phonons into higher and lower orders. Standard weak interaction theory describes diffraction in the Bragg regime as the propagation of a uniform plane wave of light through a uniform plane wave of sound, resulting in the well known first- and zeroth-order diffraction. We investigate Raman-Nath diffraction corresponding to near-Bragg diffraction. A result shows the dependence of various scattered orders on the incident angle/Bragg angle illustrating the Bessel function dependence.